Desain Undang-Undang Khusus Kekayaan Intelektual Komunal untuk Perlindungan Masyarakat Tradisional - Darwance Darwance (Jurnal Ilmiah Kebijakan Hukum, 2026)
Regulations on Communal Intellectual Property (CIP) in Indonesia are scattered across many types of legislation, rather than being contained in a single comprehensive law. This fragmentation of regulations can result in weak legal protection for traditional communities, which are the custodians of most CIP, as well as weak legal protection for the objects of CIP themselves. On the other hand, CIP is sui generis in nature. This research is normative in nature, using a regulatory and conceptual approach. This study offers a proposed design for a specific law regulating the protection of CIP by combining all types of CIP and synchronizing it with other laws related to the issue at hand, including international conventions. Therefore, this study aims to analyze the concept of CIP in several regulations, namely the Copyright Law, the Trademark and Geographical Indications Law, and the Patent Law, to subsequently construct regulations on CIP as an effort to provide optimal legal protection for the intellectual property of traditional communities. In several individual Intellectual Property Rights (IPR) laws, CIP are conceptualized in various ways, which has the potential to hinder the legal protection process, especially for traditional communities that are collective in nature. The protection of traditional communities needs to be strengthened through the drafting of legislation in the form of a law that specifically regulates CIP comprehensively, combining a number of existing regulations with several improvements, as well as synchronizing with several other laws relevant to the issue of communal intellectual property, including international conventions, one of which relates to the position of traditional communities.